Worsening of myocardial performance index in beta-thalassemia patients despite permanently normal iron load at MRI: A simple and cheap index reflecting cardiovascular involvement?. (December 2016) - Barbero, Umberto; Longo, Filomena; Destefanis, Paola; Gaglioti, Carmen Maria; Pozzi, Roberto; Piga, Antonio
Abstract: Background: Iron Overload Cardiomyopathy (IOC) due to repeated transfusions still represents the main cause of death in Thalassemia major (TM) patients. Because iron overload remains asymptomatic for long time, it is important to stratify the patients based on the risk of developing IOC before the appearance of clinical signs of heart failure. The magnetic resonance imaging (MRI) T2* may be useful but it is expensive and its MRI software has limited availability; conventional echocardiographic parameters, although easy availability, remain normal until advanced stages of IOC. Tissue Doppler Imaging (TDI) opened a new way to explore systolic and diastolic function directly or through derived index such as myocardial performance index (MPI) which has a prognostic value in different cardiomyopathies. Methods: We enrolled 46 consecutive β-TM patients without clinical signs of heart failure and we tested them with echocardiography in 2011 and again in 2015. MPI of left and right ventricular lateral wall was calculated by TDI. All TM patients had a T2* MRI evaluation of the heart in the year before. Results: Despite the absence of significant changes in morphological data at echo and at T2* evaluation, S′ waves of the lateral ventricular wall decrease while time passed, MPI worsened during the follow-up period and the derived systolic pulmonary artery systolic pressure (PAPs) increased in 2015 with respect to 2011. Conclusion: TDI and MPI may reveal very early myocardial dysfunction in TM patients despite a normal T2* value. Together with PAPs they should be periodically checked in these patients.